MARKETING STRATEGY IN EFFORTS TO IMPROVE THE QUALITY OF COMPETITIVENESS IN THE TRAVEL BUREAU OF PT. BABUL UMROH MANDIRI WISATA BRANCH BUKITTINGGI - Alwi, Hadad; Nurani, Khadijah (Multazam : Jurnal Manajemen Haji dan Umrah, 2023)
The background of this research is the number of Umrah Travel Organizers (PPIU) in various regions areas, especially umrah travel agents in the city of Bukittinggi and its surroundings. So, in this case, PT. Babul Umroh Mandiri Wisata Bukittinggi Branch can try to optimize and implement several marketing strategies through SWOT analysis to improve the quality of competitiveness. The research method used by the author is a qualitative descriptive method, starting from observation, interviews and documentation. The SWOT diagram shows that this travel is in quadrant 1 (positive, positive) supports the Aggressive Strategy. This position signifies that PT. Babul Umroh Mandiri Wisata Bukittinggi Branch is a condition that can use that power owned to take advantage of existing opportunities, so it is possible to continue to expand by implementing a maximum marketing strategy in an effort to improve the quality of competitiveness.